d-zero Magnetism in Nanoporous Amorphous Alumina Membranes - Coey, John; Esmaeily, Amir Sajad; Venkatesan, M.; Sen, S. (My University, 2018)
Nanoporous alumina membranes produced by mild or hard anodisation in oxalic acid at potentials ranging from 5 – 140 V have a controllable pore surface area of up to 200 times the membrane area. They exhibit a saturating magnetic response that is temperature-independent and almost anhysteretic below room temperature. The magnetism cannot be explained by the ~1 ppm of transition-metal impurities present in the membranes. The magnetic moment increases with the area of the open nanopores, reaching values of 0.6 Bohr magnetons per square nanometer for mild anodisation and 8 μBnm-2 for hard anodisation where the growth rate is faster. Crystallization of the membrane or chemical treatment with salicylic acid reduces the effect by up to 90 %. The magnetism is therefore associated with the open pore surfaces of the amorphous Al2O3, and it is independent of the orientation of the applied field with respect to the membrane surface. Possible explanations in terms of electrons associated with oxygen vacancies (F or F+ centres) are discussed and it is concluded that the effect is due to giant orbital paramagnetism rather than collective ferromagnetic spin order.
PUBLISHED
Keywords: d-zero magnetism; Amorphous alumina; Porous anodized alumina; Giant orbital paramagnetism; FABRICATION; NANOSTRUCTURES; Physics